Study of API Banyuwangi Seaplane Operations with Connectivity Analysis and Flight Optimization Methods for Outermost, Remote and Underdeveloped Regions in Indonesia - Hadi Prayitno*; Achmad Setiyo Prabowo; Dhian Supardam; Demmy Setyo Wiyono (Universitas Syiah Kuala, 2023)
This research examines API Banyuwangi seaplane operations in optimizing flights in Indonesia's outermost, remote, and underdeveloped regions. The connectivity analysis method measures regional connectivity with seaplane flights and identifies areas that require better accessibility. In addition, this research also involves optimizing flights by considering factors that affect seaplane operations, such as weather, topography, and distance. The results of this research can provide input for developing seaplane flight services in Indonesia, particularly in outermost, remote, and underdeveloped regions.